Feedback : Varying constant?. (1st February 2019) - Gough, William; Grozier, Jim
Abstract: In response to the feature by Benjamin Skuse "SI gets a makeover" (November 2018 pp32–35) in which he looks into the redefinition of the SI units and especially the kilogram.